Do the strength levels predict the motor coordination in young basketball players? - Soares, Jorge Pinto (2019)
The aim of this study was to analyse the relation between the strength levels and motor coordination in young basketball players. The sample of this study was composed by 12 basketball players with 15.83 (± 0.55) years old from the U-18 category. The players participate in the inter-regional, national championship round and national cup in 2015/2016 season. The upper limbs strength was evaluated with the push-up exercise, counting the number of repetitions in 30 seconds. The lower limbs strength was evaluated in centimetres with the horizontal jump without preparatory sprint. The motor coordination was evaluated with 6 cones separated by 1,5m in the diagonal. The athletes with ball, skirted the cones and ended with layup finalization, this exercise was measured in seconds. Spearman correlation test was accessed with a significance level of 5%. No significant correlation was observed between upper limbs strength and motor coordination (F =-0,259; p =0.208). However, a negative significant correlation was observed between lower limbs strength and coordination was observed (F =-0,539; p =0,035). Thus, basketball coaches should perform specific strength training seasons intending to improve the motor coordination. Improving strength levels may contribute for motor coordination improvement.